2005
DOI: 10.1007/s10616-005-3761-8
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-digested Fucoidan Extracts Derived from Seaweed Mozuku of Cladosiphon novae-caledoniae kylin Inhibit Invasion and Angiogenesis of Tumor Cells

Abstract: Fucoidan is a uniquely-structured sulfated polysaccharide found in the cell walls of several types of brown seaweed that has recently, especially as enzyme-digested fucoidan extract, attracted a lot attention due to its anti-tumor potential. In this study, we evaluated the effects of enzyme-digested fucoidan extracts prepared from seaweed Mozuku of Cladosiphon novae-caledoniae kylin on in vitro invasion and angiogenesis abilities of human tumor cells. First, we evaluated the effect of the fucoidan extracts on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
82
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(84 citation statements)
references
References 37 publications
1
82
0
Order By: Relevance
“…A number of genes that are associated with apoptotic cell death were tested in order to clarify the mechanism by which fucoidan treatment induces apoptosis in MDA-MB-231 cells. According to some previously conducted studies, caspases act as key players of fucoidan-induced apoptosis [20][21][22][23][24][25][26][27] . These findings have guided the researcher to propose a model in which fucoidan promotes apoptosis in MDA-MB-231 cells through increasing caspases activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of genes that are associated with apoptotic cell death were tested in order to clarify the mechanism by which fucoidan treatment induces apoptosis in MDA-MB-231 cells. According to some previously conducted studies, caspases act as key players of fucoidan-induced apoptosis [20][21][22][23][24][25][26][27] . These findings have guided the researcher to propose a model in which fucoidan promotes apoptosis in MDA-MB-231 cells through increasing caspases activity.…”
Section: Discussionmentioning
confidence: 99%
“…Fucoidan, a class of fucose-enriched sulfated polysaccharides, is a naturally occurring polysaccharide compound in brown alga, such as Fucus vesiculosus, Cladosiphon okamuranus and Laminaria saccharina [1,2] . It has recently been reported that fucoidan possesses a wide variety of biological activities, including anticoagulant, antiviral, antiangiogenic, anticancer and immune-modulatory activities [3] . Studies in vitro have indicated that fucoidan exhibits protection effect against various cancers, including human lymphoma, promyelocytic leukemia, colon carcinoma, breast carcinoma, hepatoma and melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, regulation of MMP-2 and MMP-9 activity remains a way of controlling cancer progression. A brown algal extract was shown to inhibit MMP activity and was proposed as a candidate antimetastatic agent as well as for use in other chronic disorders (Ye et al 2005;Kim 2006). It has been reported that a mixture of four herb extracts inhibits the invasive potential of hepatocellular carcinoma by inhibiting MMP activity (Ha et al 2004), and an approach to the development of an anticancer agent by inhibiting MMP activity has been demonstrated (Roomi et al 2006a, b, c).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that fucoidan has significant biological activities, such as anti-bacterial (2), anti-viral (3), anti-coagulant (4), anti-oxidant (5), anti-inflammatory (4,6) and immunomodulatory effects (2,7). Other studies also described anti-carcinogenic properties (8)(9)(10)(11)(12)(13)(14)(15). For example, in vitro studies demonstrated that fucoidan can inhibit cell proliferation and induce cell death in numerous cell lines, including human bile duct cancers (8), nonsmall-cell bronchopulmonary carcinoma (9) and lymphoma (10).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in vitro studies demonstrated that fucoidan can inhibit cell proliferation and induce cell death in numerous cell lines, including human bile duct cancers (8), nonsmall-cell bronchopulmonary carcinoma (9) and lymphoma (10). It is also reported to inhibit the invasion of HT1080 human fibrosarcoma cells and the angiogenic activity of HeLa human uterine carcinoma cells (11). In vivo studies have also demonstrated that fucoidan is a potent anti-neoplastic compound; and is reported to suppress the growth of Ehrlich ascites carcinoma (12,13), Lewis lung carcinoma and B16 melanoma (14), and also inhibit the metastasis of 13762 MAT rat mammary adenocarcinoma (15).…”
Section: Introductionmentioning
confidence: 99%